Spatial planning and the influence of domestic actors: Some conclusions. - Stead, Dominic; Cotella, Giancarlo (TH Zürich, NSL, 2011)
Das Heft berichtet in Länderstudien über den Stand der Europäisierung der Raumplanung in fünf Mitgliedstaaten der EU und die Rolle, die inländische Akteure auf nationaler, regionaler und lokaler Ebene bei den Wandlungsprozessen spielen. Der zusammenfassende Beitrag weist darauf hin, dass viele dieser Wandlungsprozesse ortsspezifisch, zeitgebunden und pfadabhängig sind und sich dabei die nationalen Raumplanungssysteme in Europa voneinander unterscheidet. Selbst die gemeinsamen Europäischen Debatten und Beschlüsse über Raumplanungspolitik zeigen eine große Heterogenität in den jeweiligen Auswirkungen auf mitgliedsstaatlicher Ebene und lassen kaum eine Konvergenz der Raumplanungssysteme Europas erkennen.

The papers in this special issue have all focused on the extent to which spatial planning systems develop and evolve in different domestic contexts. The contributions indicate that many processes of change are place-specific, time-contingent and sometimes path-dependent. For this reason, each national spatial planning system in Europe is distinct, with its own set of territorial institutions, planning practices and actor constellations. Each of the contributions in the volume has helped to demonstrate that common challenges and driving forces of reform to spatial planning (highlighted in the introduction to this special issue) can have differential impacts in different places, which is often due to the influence exerted by domestic actors in the process of change. Even the impacts of common European debates on spatial planning show a high degree of heterogeneity in the five case studies contained in this issue (Finland, Greece, Italy, Latvia and Portugal) and provide little evidence to suggest that spatial planning systems are converging.
Keywords: Raumplanung; Planungssystem; Planungsorganisation; Raumplanungsbehörde; Raumplanungsinstitution; Planungspraxis; Raumplanungspolitik; Europäisierung; Planungskultur; Raumplanungshoheit; Raumplanungsprogramm; Akteur; Akteursforschung; Konvergenz; Raumentwicklungspolitik; Planungsansatz; Territoriale Agenda der EU; Territoriale Governance; Governance; Harmonisierung; Planungsgeschichte